INDIKASI MEDIS DAN PENYEMBUHAN LUKA PASIEN POST HISTEREKTOMI DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Yektiningtyastuti Yektiningtyastuti; Nilasari Kusuma (LPPM STIKes Mitra Adiguna, 2026)
Hysterectomy is the most common surgical procedure for women with gynecological tumors or cancer. In the U.S., over 600,000 hysterectomies are performed annually, while Indonesia reports a prevalence of 13% to 37%. Proper wound management is crucial to preventing infection and promoting healing after surgery. This study investigates the relationship between medical indications and wound healing in post-hysterectomy patients at Prof. Dr. Margono Soekarjo General Hospital. Using a quantitative approach with a descriptive correlational design, 41 patients were selected through consecutive sampling. Bivariate analysis was conducted using the Spearman Rank Test, revealing no significant relationship between medical indications and wound healing in Stage I (days 2–3 post-surgery, p-value: 0.775) or Stage II (days 7–10 post-surgery, p-value: 0.656). These results suggest that medical indications do not significantly affect wound healing, suggesting that other factors, such as age and nutritional status, may be influential.